Sistem Pendukung Keputusan Dalam Menentukan Penjurusan Siswa Dengan Metode Simple Additive Weighting Berbasis Website - Ahmad Syahfrizal; Feri Candra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
SMA Negeri 1 Kampar Timur is one of schools in Kampar regency which every year conducts the selection of majors for their students routinely. Selection of this majors intends students can complete their education in accordance with their interests and abilities before proceed to a higher level. Currently, process of major selection in the Senior High School Level has some weaknesses. For example, process needs a long time and the obtained results are less accurate because many mistake can be happened thar caused no special available system based on a computer to support the calculation to help in determining the majors. In this research, using PHP programming system and Mysql database as database server with Simple Additive Weighting Method (SAW) by using some criterion, suck as previous subject values in Junior High School (Natural Sciences and Social Sciences), the result of enterance test in the Senior High School, students interest, parents and counseling guidance teacher advice are used in this research. Final result of this research is a decision that is able to assist process of choosing the majors in SMA Negeri 1 Kampar Timur. Result of system test accuracy obtained is 93.18% of the 352 data tested. It indicates that Decision Support System can work successfully according to Simple Additive Weighting Method (SAW).Keywords : Decision Support Systems, Selection Majors Criteria, Simple Additive Weighting.